Single-port video-assisted thoracoscopic surgery lung resection: experiences in Fujian Medical University Union Hospital - Zhu, Yong; Xu, Guobing; Zheng, Bin; Liang, Mingqiang; Wu, Weidong; Zheng, Wei; Chen, Chun (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
Video-assisted thoracoscopic surgery (VATS) is currently a better choice than thoracotomy for lung resection, and then single-port VATS has been increasingly applied in clinical settings with the improvements in both endoscopic instruments and surgical skills. Our center began to perform single-port VATS lobectomy in May 2014 and had performed all sort of lung resection in 168 patients till December 2014, including wedge resection, routine lobectomy, sleeve lobectomy, segmentectomy and pneumonectomy. All these procedures were successfully performed without any severe complication. We believe the single-port VATS lung resection is a safe and feasible procedure after surgery practice.